Aventuras em quantópolis: elaboração e utilização de livro paradidático para abordagem conceitual do modelo padrão de física de partículas em turmas do ensino médio - Braga, Francisco Levi Pereira (2018)
The last century was much developed to Science. The discoveries of the new particles which never were imagined they shaked the comfortable feeling about the subatomic world’s knowledge, showing which still there is much things to studying about it. Once physics teacher in high school, we start to catch sight how to treating these new things into a curriculum that works of emphatic way the phenomenon that occur to low speeds and large dimensions. Thus, it was prepared an educational book which tells a student’s history that in class he was very curious about the existence of a microscopic world and during a dream he has the opportunity to knowing the most diverse particles made of substance that surround him, As well as its alterations, learning quantum mechanics’ physical concept, without sticking its mathematical rigor. To verifying the acceptable of material, this was used to the 3rd grade of high school and integral time José de Borba Vasconcelos in Maracanaú-Ceará. Among the actions to applicate the product, besides its reading we can mention like special the assembly of plays which provide playful moments of great involvement among the students. This verified itself with the initiative that the school rooms’ development which had access the material they improved very much comparing with the school rooms’ development that had access the traditional method of application of content, evidencing which the new practices of teaching both about the new materials like new pedagogies too, it aiming a effective participation in the knowledge construction and all this can contribute to a greater success in the process of teaching and learning